2000
DOI: 10.1046/j.1365-2222.2000.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of hay fever and asthma among children of farmers

Abstract: Factors related to environmental influences on a farm such as increased exposure to bacterial compounds in stables where livestock is kept prevent the development of allergic disorders in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
440
17
13

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(512 citation statements)
references
References 27 publications
42
440
17
13
Order By: Relevance
“…Estimates from the video questionnaire for the prevalence of wheeze in the previous 12 months were even lower, ranging 1.3-3.3% for the centres in China, whereas the global mean was 7.3%. The low prevalence of asthma-like symptoms and reported asthma in rural areas in China is consistent with recent reports of the scarcity of asthma and atopy among children raised on farms in several countries [7][8][9][10][11]. It has been postulated that the lifestyle associated with living on a farm (larger family size, more pets, heating frequently using wood or coal, less maternal smoking and more dampness) may be responsible for the low prevalence.…”
Section: Discussionsupporting
confidence: 85%
“…Estimates from the video questionnaire for the prevalence of wheeze in the previous 12 months were even lower, ranging 1.3-3.3% for the centres in China, whereas the global mean was 7.3%. The low prevalence of asthma-like symptoms and reported asthma in rural areas in China is consistent with recent reports of the scarcity of asthma and atopy among children raised on farms in several countries [7][8][9][10][11]. It has been postulated that the lifestyle associated with living on a farm (larger family size, more pets, heating frequently using wood or coal, less maternal smoking and more dampness) may be responsible for the low prevalence.…”
Section: Discussionsupporting
confidence: 85%
“…One hypothesis is that the farming environment has a stimulatory impact on the developing immune system that may confer protection from allergic disease. Allergy-protective effects of a farming lifestyle have previously been reported by large epidemiological questionnaire-based studies regarding clinical diagnosis of allergy (29,30). Indeed, even though a relatively low number of study subjects were included in this cohort, we show that the prevalence of allergic disease, but not sensitization, is significantly reduced in children raised on a dairy farm compared with nonfarmers' children who lived on the countryside.…”
Section: Discussionsupporting
confidence: 53%
“…2A). The prevalence of allergy is reduced in children raised on dairy farms (29,30). In this study, we found a significantly lower prevalence of allergic disease, but not sensitization, at both 18 and 36 mo of age among farmers' children compared with nonfarmers' children (Supplemental Fig.…”
Section: High Proportions Of Cd5 + B Cells Are Positively Associated mentioning
confidence: 48%
“…16 In turn, endotoxin exposure confers protection on the development of allergy and asthma. 17 While no prior studies have evaluated this effect in our gene of interest, TLR6, both TLR6 and TLR4 elicit similar cytokine responses upon exposure to bacteria, 18 suggesting that alterations in TLR6 may result in a phenotype similar to that of TLR4. Interestingly, human mast cells express mRNA for TLR6.…”
Section: Resultsmentioning
confidence: 98%